1993
DOI: 10.1007/bf01303170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral cyclosporin on renal function in Crohn's disease

Abstract: Twenty-one patients with Crohn's disease were followed prospectively for 24 weeks to examine the effect of a low-dose cyclosporin regime on renal function (initial dose 5 mg/kg reduced by 1 mg/kg every two months to a maintenance of 2 mg/kg). Glomerular filtration rate (GFR) and effective renal plasma flow (ERPF) were measured by radioisotope clearance at 0, 6 and 24 weeks. GFR and ERPF fell significantly (mean GFR at baseline: 120.9 ml/min/1.73 m2; at six weeks: 100.9 ml/min/1.73 m2; mean ERPF at baseline: 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Irreversible reduction of glomerular filtration may be associated with its chronic use and interstitial fibrosis is reported in 20% of patients with normal preexisting renal function treated for autoimmune disease. [12][13][14] The development of opportunistic infections, including Pneumocystis carinii, may be related to the degree of immunosuppression, especially when corticosteroids are used concurrently.I5 Neurological disturbances including paraesthesia and tremor are common, and grand ma1 seizures are reported in 1 5 5 . 5 % of transplant recipients.I6 Mild reversible impairment of liver function, hypertension, hyperlipidaemia, hyperkalaemia and hyperuricaemia are less common.1o In our experience, adverse effects were frequent, though most of these were mild and transient.…”
Section: Discussionmentioning
confidence: 99%
“…Irreversible reduction of glomerular filtration may be associated with its chronic use and interstitial fibrosis is reported in 20% of patients with normal preexisting renal function treated for autoimmune disease. [12][13][14] The development of opportunistic infections, including Pneumocystis carinii, may be related to the degree of immunosuppression, especially when corticosteroids are used concurrently.I5 Neurological disturbances including paraesthesia and tremor are common, and grand ma1 seizures are reported in 1 5 5 . 5 % of transplant recipients.I6 Mild reversible impairment of liver function, hypertension, hyperlipidaemia, hyperkalaemia and hyperuricaemia are less common.1o In our experience, adverse effects were frequent, though most of these were mild and transient.…”
Section: Discussionmentioning
confidence: 99%
“…27 A few case reports dealing w ith severe and sometimes fatal opportunistic infections have been reported. [23][24][25][26] Importantly, these infections occurre d during high-dose cyclosporine treatme nt in combination with corticoste roids.…”
Section: Side Effects and Toxicitymentioning
confidence: 99%
“…Being a powerful immunosuppressant, cyclosporine also has potential side effects including: renal insufficiency (6%), hyperte nsion (11%), infectious complications (3%), severe neurological disorders including epilepsy (1%), paresthesias (26-70%), tre mor (7%), headache (5%), hypertrichosis (13%), gingival hyperplasia (2%), and anaphylax is (0.3%) [23][24][25][26] (Table 1).…”
Section: Side Effects and Toxicitymentioning
confidence: 99%
“…This is thought to be related to vasoconstriction and a decrease in afferent arteriolar blood flow. Nephrotoxicity may present as reversible dysfunction, irreversible acute renal failure, chronic renal insufficiency, hyperchloremic hyperkalemic acidosis, and thrombotic microangiopathy (55). Almost all patients with IBD receiving chronic cyclosporine therapy demonstrate a 20% decline in their effective renal plasma flow and glomerular filtration rate, which is reversible within 2 weeks of discontinuation of therapy.…”
Section: Drug Nephrotoxlcitymentioning
confidence: 99%
“…However, patients with CD treated with lowdose (4 mg/kg/day) cyclosporine given orally do not experience major changes in renal hemodynamics. Serum levels of BUN and creatinine may increase, although often within the normal range (55). However, a recent study of renal biopsy data suggested that histopathologic evidence of nephropathy is found in 21% of patients and includes arteriolopathy (2%), interstitial fibrosis (5%) and tubular atrophy (1.5%) (56).…”
Section: Drug Nephrotoxlcitymentioning
confidence: 99%